Pituitary apoplexy in pregnancy: a case report. (18th April 2012) - Roche-Kelly, E; MacKillop, L; Hanna, G; Pandey, S
Abstract : Introduction: Pituitary apoplexy is a clinical syndrome of selective or multi-hormonal pituitary failure, classically described as a result of infarction of a pre-existing pituitary adenoma associated with pituitary or peri-pituitary haemorrhage. Previous reports in pregnancy have described pituitary apoplexy complicating macroprolactinomas, growth-hormone secreting tumours, and auto-immune lymphocytic hypophysitis. Radiological diagnosis is difficult, particularly with the reticence to use contrast media in pregnancy. In addition, the profound changes in most pituitary axes during pregnancy complicate interpretation of hormone levels. Case study: MI, a 31-year-old with three previous low-risk pregnancies, presented with recurrent new-onset unexplained collapse from 28- to 33-weeks gestation. The history was suggestive of vaso-vagal episodes; precipitated by headache, or prolonged standing. However, progressive frequency, spontaneous onset at rest and generalised seizure activity necessitated further investigation. Electrocardiogram, echocardiogram and continuous cardiac monitoring during episodes demonstrated no cardiological cause. No neurological deficit was demonstrated. Following transfer to a tertiary centre, magnetic resonance imaging identified changes in-keeping with acute haemorrhage within an enlarged pituitary gland, consistent with pituitary apoplexy. A short synacthen test suggested sub-optimal pituitary-adrenal axis function. No other pituitary deficiency was demonstrated. MI was treated medically with steroid replacement therapy and proceeded to term with emergency caesarean section for failure to progress. Discussion: Hypopituitarism can present insidiously with variable involvement of trophic hormonal axes. It is plausible that the increased frequency and severity of the episodes was a presenting feature of progressive corticotrophin deficiency, reinforced by clinical improvement on steroid replacement.